Komunikasi Dalam Keluarga dan Asertifitas Remaja Penyalahguna Narkoba - Hasanah, Uswatun; Arista, Irfani; Silitonga, Mirdat (Puslitbangkesos Kementerian Sosial RI, 2020)
Drug abuse is a quite serious problem and its handling involves various stakeholders. This study aims to analyze how the influence of family communication on the assertiveness of adolescent drug abusers. This study used a cross-sectional study design and was carried out at National Narcotics Agency, Jakarta Timur City (BNNK), Jakarta Timur and Non-Governmental Organizations under the guidance of the BNNK, Jakarta Timur namely: Balarenik Foundation and Swara Peduli Indonesia Foundation. The selection of research locations is done by snowball sampling. The population of this study is adolescent drug abusers inÂ Â Jakarta Timur, Jakarta. The respondents of this study were 68 adolescent drug abusers in BNNK, Jakarta Timur, Balarenik Foundation, and Indonesian Swara Care Foundation. The sampling technique in this study uses non-probability sampling with purposive sampling. The findings in this study are that there is a significant positive effect of family communication on adolescent assertiveness. The determinant coefficient in this study was 62%, which means that the assertiveness of adolescent abusers of narcotics is determined by the communication of the of family of 62% and 38% is determined by other factors.